2013
DOI: 10.19026/ajfst.5.3074
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds of Palm Fatty Acid Distillate (PFAD) from Several Palm Oil Refineries

Abstract: This research studied the characteristics of Palm Fatty Acids Distillates (PFADs) from several palm oil refineries. It was aimed to know the potency of PFAD as bioactive compounds source, including vitamin E (mainly tocotrienols), phytosterols, squalene and possibly co-enzyme Q10 and polycosanol. Sampling was conducted at 6 palm oil refineries. The results showed that PFAD was dominated by free fatty acids of 85-95% with low oxidation level indicated by peroxide value of 1-10 meq/kg and anisidin value of 6-31.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
11
0
5
Order By: Relevance
“…Palm oil contained vitamin E 600-1.000 ppm, phytosterols 300-620 ppm, carotenoid 500-700 ppm, squalene 250-540 ppm, phospholipids 20-100 ppm, co-enzyme Q10 10-80 ppm, and poliphenol 40-70 ppm [18]. Meanwhile, our previous study [27] showed that PFAD from several palm oil refineries contained vitamin E 65-281 ppm, phytosetrols 407-6012 ppm, and squalene 206-1274 ppm. Vitamin E of PFAD comprised of α-tocopherol 9-135 ppm, α-tocotrienol 12-52 ppm, δ-tocotrienol 5-64 ppm, γ-tocotrienol 32-118 ppm.…”
Section: Bioactive Compounds Of Pfadmentioning
confidence: 99%
“…Palm oil contained vitamin E 600-1.000 ppm, phytosterols 300-620 ppm, carotenoid 500-700 ppm, squalene 250-540 ppm, phospholipids 20-100 ppm, co-enzyme Q10 10-80 ppm, and poliphenol 40-70 ppm [18]. Meanwhile, our previous study [27] showed that PFAD from several palm oil refineries contained vitamin E 65-281 ppm, phytosetrols 407-6012 ppm, and squalene 206-1274 ppm. Vitamin E of PFAD comprised of α-tocopherol 9-135 ppm, α-tocotrienol 12-52 ppm, δ-tocotrienol 5-64 ppm, γ-tocotrienol 32-118 ppm.…”
Section: Bioactive Compounds Of Pfadmentioning
confidence: 99%
“…DD is an excellent source in this respect as it contains valuable products like phytosterols, tocopherols, sterols and hydrocarbons (mainly squalene), which can be recovered and isolated as food additives [3][4][5] . Different DDs or fatty acid distillates are used for this purpose like soybean, canola and sunflower 6,7 , palm [8][9][10] , rice bran oil 11 etc. SODD has been considered as an important source for the preparation of functional foods such as STC.…”
Section: Research Articlementioning
confidence: 99%
“…PFAD berwarna cokelat, berbau khas dan berbentuk padat pada temperatur ruang (Hasibuan dan Siahaan, 2013). PFAD mengandung 85-95% asam lemak bebas dengan asam palmitat dan asam oleat sebagai komponen terbesar dan komponen lain berupa triasilgliserol, gliserida parsial dan fraksi yang tidak tersabunkan seperti vitamin E, sterol dan squalen (Ping and Yusof, 2009;Estiasih et al, 2013). PFAD berpotensi digunakan sebagai bahan baku produk pangan, non pangan dan nutrisi serta kesehatan.…”
Section: Pendahuluanunclassified